Optimising environmental product life cycles: A case study of the European pulp and paper sector - Paul M. Weaver; H. Landis Gabel; Jacqueline M. Bloemhof-Ruwaard; Luk N. Van Wassenhove (Fondazione Eni Enrico Mattei (FEEM), 1997)
In this paper, we propose a methodology, based on materials accounting and operational research techniques, to assess different industry configurations according to their life cycle environmental impacts. Rather than evaluating a specific technology, our methodology searches for the feasible configuration with the minimum impact. This approach allows us to address some basic policy-relevant questions regarding technology choice, investment priorities, industrial structures, and international trade patterns. We demonstrate the methodology in the context of the European pulp and paper industry. We are able to show that current environmental policy's focus on maximising recycling is optimal now, but that modest improvements in primary pulping technology may shift the optimal industry configuration away from recycling toward more primary pulping with incineration. We show that this will have significant implications for the amount and type of environmental damage, for the location of different stages in the production chain, and for trade between European member states. We caution policy makers that their single-minded focus on recycling may foreclose investment in technologies that could prove environmentally superior. Finally, we hint that member state governments may be fashioning their environmental policy positions at least in part on some of the trade and industrial implications we find.
Keywords: Q2; C6; 330; Environmental policy; Pulp and paper; Life cycle; Optimisation; Technology lock-in; Recycling; Geography of production; Environment-trade conflict